Design and Development of an IoT (Internet Of Things)-Based Temperature and Humidity Control System for Hamster Cages - Affandi, Eko Kholid; Rahmawati, Diana; Ulum, Miftachul; Joni, Koko; Purnamasari, Dian Neipa; Hardiwansyah, Muttaqin (Universitas Panca Marga, 2024)
Hamsters are generally healthy creatures and can live about two years or more. They need a comfortable cage with a temperature of 17oC to 23oC and for humidity is 40 RH% to 70 RH% which sometimes these things are neglected by hamster owners. If the temperature and humidity are not appropriate it can cause disease in hamsters even to the death of hamsters. So a tool is needed to stabilize temperature and humidity. In this system using themethod (Hybrid Proportional Integral Derivative - Artifical Neural Network (PID-ANN) where the method is a combination of PID and ANN methods as a determinant of PID parameters, namely Proportional Constants, Integral Constants and Derivative Constants automatically with the help of ANN tuning. as temperature and humidity stabilizers. The inputs in this method are temperature and humidity obtained from the DHT22 sensor. While the output in this study is in the form of analog values for dimmer control controlling lux on incandescent lamps and humidifiers. This system is also based on the internet of things so that it can be monitored and controlled in real time. So that it can be used anywhere and anytime